SUN IN PERSPECTIVES OF SCIENCE AND AL-QUR’AN - Mahmudah, Fitri; Rahmatika, Resty (http://jagadalimussirry.com/, 2020)
Abstract. This study aims to find out the function of the sun in the perspective of science and the Qur'an. The research method used is qualitative research methods with the type of library research (Library Research). The results of this study are, scientific theories explain the function of the sun in accordance with what is explained in the verses of the Qur'an. Science explains that the sun as the largest source of light energy for the earth can produce its own energy. This is explained in the Qur'an that the sun is described as siraj and dhiya 'which means sunlight comes from itself, and as the center of the solar system with the sun's gravitational force not static but also moving, this is in the Koran explained in (QS Yasin verse 38; QS Noah verse 16), besides that science and the Koran also equally explain that the sun as a process of photosynthesis (QS At-Takwir verse 18; QS Thaha verse 53) and the sun can be used as a time calculation (QS Al-An'am verse 96).